Efecto antibacteriano in vitro del aceite esencial de Origanum vulgare “orégano” sobre Streptococcus Pyogenes. - Delgado Nicolás, Héctor Diego (2019)
OBJECTIVE: To evaluate the in vitro antibacterial effect of the essential oil of Origanum vulgare (EOOV) on Streptococcus pyogenes. MATERIAL AND METHODS: Experimental study of the antibacterial effect of the concentrations at 25%, 50%, 75% and 100% of the EOOV on Streptococcus pyogenes; Penicillin G Benzathine is used as a positive control and Tween80 as a negative control. The Kirby Bauer method and the minimum inhibitory concentration (MIC) were used to evaluate the antibacterial activity. The calculation of the standard deviation was used, the coefficients of variation were evaluated and the multiple comparisons test was used using homogeneous subsets; all with a level of significance of 0.05 (P <0.05). RESULTS: The susceptibility of Streptococcus pyogenes to EOOV was 15.17mm, 15.33mm, 16.08mm and 18.75mm at 25%, 50%, 75% and 100% respectively and the MIC of EOOV was 25% (230.81mg / mL). Likewise, strains of Streptococcus pyogenes showed "average sensitivity" to the AEOV groups of 75% and 100% in 100% and to the EOOV groups of 25% and 50% in 83% and 92% respectively. CONCLUSION: There is an antibacterial effect of EOOV on Streptococcus pyogenes isolated from pharyngeal swab.